2011
DOI: 10.1209/0295-5075/94/11002
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the effect of hyperonic three-body forces on the maximum mass of neutron stars

Abstract: PACS 13.75.Ev -Hyperon-nucleon interactions PACS 26.60.Kp -Equations of state of neutron-star matter PACS 26.60.-c -Nuclear matter aspects of neutron stars PACS 97.60.Jd -Neutron stars

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
210
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(221 citation statements)
references
References 55 publications
8
210
3
Order By: Relevance
“…[30,31]) are scarce. This lack of experimental information induces large uncertainties within the microscopic approaches [11][12][13], which suffer in addition probably from theoretical shortcomings, among others due to the unknown hyperonic threebody forces [32]. Phenomenological extrapolations of the low-density behavior within mean field models are subject to large uncertainties, too.…”
Section: Introductionmentioning
confidence: 99%
“…[30,31]) are scarce. This lack of experimental information induces large uncertainties within the microscopic approaches [11][12][13], which suffer in addition probably from theoretical shortcomings, among others due to the unknown hyperonic threebody forces [32]. Phenomenological extrapolations of the low-density behavior within mean field models are subject to large uncertainties, too.…”
Section: Introductionmentioning
confidence: 99%
“…Since then the ΛNN interaction received considerable attention in many other studies of hypernuclei [35][36][37][38][39][40][41][42][43]. It is thus quite natural to expect that YTBIs can influence the EoS of dense matter and can represent a likely candidate to solve the hyperon puzzle [45][46][47][48]. This idea was advocated [49] even before the measurements of NSs with M ∼ 2 M sun [2,3].…”
Section: Hyperon Starsmentioning
confidence: 99%
“…Assuming that the strength of these interactions is either smaller or as large as the pure nucleonic ones, the authors of [45] found that in the most favourable case the relative increase of M max due to YTBIs is ∼ 16% and the largest value of M max for hyperon stars is ∼ 1.6M sun .…”
Section: Hyperon Starsmentioning
confidence: 99%
“…This has to be ascribed to the combination of an incomplete knowledge of the forces governing the system (in the hypernuclear case both two-and three-body ones), and to the concurrent use of approximated theoretical many-body techniques. Some classes of methods extended to the hyperonic sector predict the appearance of hyperons at around 2 − 3ρ 0 , and a strong softening of EOS, implying a sizable reduction of the maximum mass [36][37][38][39]. On the other hand, other approaches suggest much weaker effects arising from the presence of strange baryons in the core of the star [40][41][42][43][44][45].…”
Section: Neutron Matter At High Densitymentioning
confidence: 99%